The causal order of job satisfaction of employee at Hicom Automotive Manufacturers Malaysia (HAMM) / Musliha Musman ... [et al.] - Musman, Musliha; Mod Arifin, Nur Nariza; Md Zain, Siti Rokyah; Mohd Surtar, Nur Nasya (2015)
The purpose of this study is to evaluate the causal order of job satisfaction among employees at Hicom Automotive Manufacturers Malaysia (HAMM) through the relationship between variables such as work stress, payment and social support. The research was conducted using a set of questionnaire and total of 150 samples had been taken for the analysis. The empirical results show that payment and social support do have a significant relationship towards job satisfaction. Meanwhile, works stress does not have significant relationship towards job satisfaction.